2013
DOI: 10.1007/s11552-013-9585-7
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radius Fractures and the Volar Lunate Facet Fragment: Kirschner Wire Fixation in Addition to Volar-Locked Plating

Abstract: Background The volar lunate facet fragment of a distal radius fracture may not be stabilized with volar-locked plating alone due to the small size and distal location of the fragment. Identification and stabilization of this small fragment is critical as unstable fixation may result in radiocarpal and radioulnar joint subluxation. The addition of spring wire fixation with volar plating can provide stable internal fixation of this critical fracture fragment. Methods A retrospective review (2006)(2007)(2008)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Fragment-specific fixation systems are available [15,16]. Hook plate, Kirschner wires and osteosuture may be also suitable techniques [17,18]. In the case of a small palmar marginal rim fragment, fixation with a volar rim distal radius plate can be a valid treatment option [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragment-specific fixation systems are available [15,16]. Hook plate, Kirschner wires and osteosuture may be also suitable techniques [17,18]. In the case of a small palmar marginal rim fragment, fixation with a volar rim distal radius plate can be a valid treatment option [19].…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty of fixation of the palmar lunate facet fragment has been recognized previously [1,2]. Stable fixation of a small palmar lunate facet fragment with a classical palmar plate alone can be insufficient and alternative fixation techniques may be necessary [15][16][17][18][19]. As the prevalence of palmar lunate facet fractures may be relatively high in intra-articular distal radius fractures, a preoperative CT-scan seems to be justified to help surgeons to decide which fixation technique is best to avoid secondary fracture displacement.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies reported reduction loss of VLF fragments in patients with distal radius fracture and small VLF fragments located very distal to the watershed line, even with the use of a distally placed volar locking plate 4,5,8,9,12 or absorbed, resulting in UV reduction loss (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported good clinical results and efficacy for distally placed plate fixation 4,5,8 11 . However, some studies noted reduction loss of the VLF fragment or distal radioulnar joint (DRUJ) instability in patients with small VLF fragments, even after treatment with a distally placed volar locking plate 4,5,8,9,12 . One study reported that a small, distally located VLF fragment could not be stabilized with volar distally placed locking plate fixation alone 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Intra-articular DRF (IDRF), a severe form of DRF, accounts for about 25% of total DRF [3]. Currently, it is still very challenging to completely recover from the IDRF, because it is necessary to achieve not only an anatomical reduction [4,5], i.e., complete reconstruction of radius and the articular surface [6], but also a strong and precise internal fixation to facilitate early rehabilitation [7]; otherwise complications such as traumatic arthritis will often occur, which will seriously affect the function of the hands and wrists [8,9].…”
Section: Introductionmentioning
confidence: 99%